Management of cervical cancer stage Ib1 with poor prognosis during pregnancy: two case reports - Kufelnicka-Babout, Maja; Kolasa-Zwierzchowska, Dorota; Stachowiak, Grzegorz; Zielińska, Małgorzata; Romanowicz-Makowska, Hanna; Kałużynski, Andrzej; Kulig, Andrzej; R. Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2012)
The therapeutic approach in cervical cancer diagnosed during pregnancy is ethically controversial due to a conflict of interest between the mother and the fetus. We present cases of two pregnant patients with invasive cervical cancer who underwent radical surgery in the Department of Gynecology and Oncology at the Polish Mother’s Institute in 2011. The aim of this study is to present the mainstay of treatment of pregnant patients with poor prognosis cervical cancer diagnosed in gestation.